Replace or remake ? A work in progress - Marie-Hélène Breuil (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Le term remake has only been used relatively recently in debates surrounding the conservation and restoration of contemporary art. The status of the « remade » work is not always very clear, wavering between exhibition copy, duplicate and reconstitution, depending on the author of the remake and the context of the reproduction.